2017
DOI: 10.1007/s13197-017-2696-3
|View full text |Cite
|
Sign up to set email alerts
|

Technological and sensorial role of yeast β-glucan in meat batter reformulations

Abstract: This study shows that apart from acting as nutritional value improver, yeast β-glucan can be successfully used to reformulate meat products. When added to meat batters, yeast derived ingredients containing β-glucans (GOLDCELL IY B and GOLDCELL BETA GLUCAN) improved the emulsifying capacity (up to 5 increments), the water holding capacity (up to 8 increments) as well as the emulsion stability. A decrease in total fluid release up to 4.30% and 3.99%, respectively with GOLDCELL IY B and GOLDCELL BETA GLUCAN respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
2
10
0
1
Order By: Relevance
“…Similar results are presented in the work by Fernández‐Ginés, Fernández‐López, Sayas‐Barberá, and Pérez‐Álvarez (), and Talukder (). The results of this study are similar to those of a study by Apostu, Mihociu, and Nicolau (), in which the WHC values of meat batter with yeast β‐glucan was significantly higher than those of model meat emulsions without β‐glucan preparates.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results are presented in the work by Fernández‐Ginés, Fernández‐López, Sayas‐Barberá, and Pérez‐Álvarez (), and Talukder (). The results of this study are similar to those of a study by Apostu, Mihociu, and Nicolau (), in which the WHC values of meat batter with yeast β‐glucan was significantly higher than those of model meat emulsions without β‐glucan preparates.…”
Section: Resultssupporting
confidence: 90%
“…The WHC values of analysed burgers during storage in modified atmosphere are presented in (2013). The results of this study are similar to those of a study by Apostu, Mihociu, and Nicolau (2017), in which the WHC values of meat batter with yeast β-glucan was significantly higher than those of model meat emulsions without β-glucan preparates.…”
Section: Ph Whc and Colour Parameterssupporting
confidence: 89%
“…A β-glucana também tem sido estudada na formulação de produtos cárneos, conforme relatado por Apostu et al (2017) que avaliaram as alterações tecnológicas e sensoriais de massa cárnea destinada a produção de derivados adicionadas de 0,5% a 3% de β-glucana comercial isolada de leveduras. Os autores verificaram que o produto apresentou maior capacidade de retenção de água e capacidade de emulsão, mantendo a coesividade e causando ligeira diminuição na dureza do produto.…”
Section: Desenvolvimento β-Glucanasunclassified
“…These fibre ingredients are non-digestible polysaccharides that can be obtained from vegetables [ 4 ], edible mushrooms [ 9 ], and microorganisms [ 10 ]. One example is inulin, a soluble dietary fibre with different levels of polymerisation.…”
Section: Introductionmentioning
confidence: 99%
“…β-Glucan is another non-starch polymer that is primarily composed of the linear polysaccharide (1→3), (1→4)-β-D-glucan and can be obtained from vegetables or mushrooms [ 12 ]. The addition of cereal β-glucans to food matrices has been demonstrated as beneficial in modifying the textural properties and improving the stability of emulsions during storage, and these benefits are based mainly on the ability of these compounds to increase the viscosity of aqueous solutions and to form stable gels [ 9 ]. Finally, Álvarez et al [ 7 ] demonstrated the use of vegetable by-products such as rice bran or walnuts to improve the textural quality and gelling properties of meat products.…”
Section: Introductionmentioning
confidence: 99%